Image Analysis of Butterfly Wing Surfaces for the Creation of New Biomimetic Materials - Marina Simovic-Pavlovic; Aleksandra Radulović; Darko Janković; Darko Vasiljević; Maja Pagnacco (Proceedings)
The biological structures of different butterfly wings were examined in terms of the analysis of their surfaces [...]